Le rôle des provinces dans les relations internationales - Jacomy-Millette, Annemarie (Études internationales, 1979)
Within the shifting context of international relations — official and transnational - of the last quarter of the XXth century, it would be appropriate to take a fresh look at the opening of federal states with special emphasis on the Canadian provinces. This opening poses political, economic, social, cultural and juridical problems, both national and international. The author conceptualizes the problem in three aspects : international organizations, international representation and international treaties. She offers suggestions and recommendations with a view to a greater decentralization of Canada's foreign policy.